2014
DOI: 10.5194/hessd-11-8167-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limitations of fibre optic distributed temperature sensing for quantifying surface water groundwater interactions

Abstract: Abstract. Studies of surface water–groundwater interactions using fiber optic distributed temperature sensing (FO-DTS) has increased in recent years. However, only a few studies to date have explored the limitations of FO-DTS in detecting groundwater discharge to streams. A FO_DTS system was therefore tested in a flume under controlled laboratory conditions for its ability to accurately measure the discharge of hot or cold groundwater into a simulated surface water flow. In the experiment the surface water (SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, it is generally acknowledged that widespread use of FO-DTS systems for environmental applications really took off after the publication by Selker et al (2006) who cited examples of this technology in surface water applications. Following Selker's earliest work, many studies have provided further understanding of the capabilities and limitations of FO-DTS instrumentation (Roshan et al, 2014;, calibration and validation of temperature observations (Hausner et al, 2011;Van De Giesen et al, 2012), analysis, and overcoming artifacts of field deployments in data sets (Arnon et al, 2014;Hilgersom et al, 2016;Neilson et al, 2010). As the technology and researchers' understanding of the systems matured, an increasing number of applications of FO-DTS to environmental investigations has followed.…”
Section: Adoption Of Fiber-optic Sensing For Environmental Sciences Amentioning
confidence: 99%
“…However, it is generally acknowledged that widespread use of FO-DTS systems for environmental applications really took off after the publication by Selker et al (2006) who cited examples of this technology in surface water applications. Following Selker's earliest work, many studies have provided further understanding of the capabilities and limitations of FO-DTS instrumentation (Roshan et al, 2014;, calibration and validation of temperature observations (Hausner et al, 2011;Van De Giesen et al, 2012), analysis, and overcoming artifacts of field deployments in data sets (Arnon et al, 2014;Hilgersom et al, 2016;Neilson et al, 2010). As the technology and researchers' understanding of the systems matured, an increasing number of applications of FO-DTS to environmental investigations has followed.…”
Section: Adoption Of Fiber-optic Sensing For Environmental Sciences Amentioning
confidence: 99%
“…< 1 md -1 vertical flux to 401 stream) zones primarily depends on locating the GW thermal signature before complete SW 402 mixing. Under controlled flume conditions, Roshan et al, (2014) found that an empirical relation 403 to quantify GW seepage could be developed based on the apparent temperature response of FO-404 DTS measurements made along the streambed interface, although this quantification would 405 likely be more difficult in uncontrolled natural settings. We therefore suggest use of TIR and FO-406 DTS for spatial identification of GW seepage locations, with qualitative comparison of relative 407 seepage rates based on the magnitude and other characteristics of thermal anomalies.…”
Section: The Impacts Of Seepage Spatial Distribution and Swcharacteristicsmentioning
confidence: 99%